Correction of running waves equations - Лёзов, П.П. (Radiotekhnika, 2012)
A pair of traversal running electromagnetic wave equations is considered and it is shows that the title "running" is given without a reason. The inclusion of spatial coordinates in the phase of the harmonic function of time does not provide movement in space, but only increases the step and decreases the oscillations frequency. The running electromagnetic wave is the most naturally described by the spiral function of time of the spatial coordinate in the direction of the wave movement as a combination of the magnetic traversal vortex and longitudinal-propagating electric field.